St Helena Marine Water Quality: Background Conditions and Development of Assessment Levels for Coastal Pollutants - Painting, Suzanne Jane; Haigh, Eleanor K.; Graham, Jennifer A.; Morley, Simon A.; Henry, Leeann; Clingham, Elizabeth; Hobbs, Rhys; Mynott, Frances; Bersuder, Philippe; Walker, David I.; Stamford, Tammy (Frontiers in Marine Science, 2021)
St Helena is an isolated oceanic island located in the tropical South Atlantic, and knowledge of broadscale oceanography and productivity in its surrounding waters is limited. This study used data from model outputs (2007-2017), remote sensing data (1998-2017) and survey measurements (April 2018 and 2019) to determine background conditions for nutrients, chlorophyll and suspended particulate matter (SPM) in offshore waters and propose standards (thresholds) for assessing inshore water quality based on 50 % deviation from seasonal (usually June to November) or annual averages. Seasonal thresholds were proposed for surface nitrate (average 0.18 µM), phosphate (average 0.26 µM), silicate (average 2.60 µM), chlorophyll (average 0.45 µg chl l-1) and SPM (average 0.96 mg l-1). Associated background values for most surface parameters (phosphate 0.17 µM, silicate 1.57 µM, chlorophyll 0.30 µg chl l-1; from model outputs and remote sensing) were slightly higher than offshore observations (April 2019). For nitrate, the average background value (0.12 µM) was lower than the observed average (0.24 µM). At depth (150-500 m), annual background values from model outputs were high (nitrate 26.8 µM, phosphate 1.8 µM, silicate 17.3 µM). Observed water masses at depths >150 m, identified to be of Antarctic and Atlantic origin, were nutrient-rich (e.g. 16 µM for nitrate, April 2019) and oxygen deficient (<4-6 mg l-1). A thermocline layer (between ca. 10 m and 230 m), characterised by a sub-surface chlorophyll maximum (average 0.3-0.5 µg chl l-1) near the bottom of the euphotic zone (ca. 100 m), is likely to sustain primary and secondary production at St Helena. For assessing inshore levels of chemical contaminants and faecal bacteria estimated from survey measurements, standards were derived from the literature. A preliminary assessment of inshore observations using proposed thresholds from surface offshore waters and relevant literature standards indicated concerns regarding levels of nutrients and faecal bacteria at some locations. More detailed modelling and/or field-based studies are required to investigate seasonal trends and nutrient availability to inshore primary producers and to establish accurate levels of any contaminants of interest or risk to the marine environment.